Light-emitting devices using micromachined Si-tip mirror arrays - Lee, YH; Lee, SJ; Ju, BK; Oh, MH (ELSEVIER SCIENCE SA, 2000)
In this paper we introduce a new structure and process scheme to generate visible light by the combination of Si-tip reflectors with thin film electroluminescent structure and report preliminary results of light emission observed from the structure. As a result, 3600 reflectors were formed within one pixel and these picture elements create a well-concentrated visible light around the point reflectors under a bipolar pulse excitation. Even though the absolute luminance level is not very high, this result is very interesting because the front emission observed by a viewer originated intrinsically from the edge emission. The new devices suggested will contribute to the development of a high-bright micro-display with the integrated drivers. (C) 2000 Elsevier Science S.A. All rights reserved.
Keywords: EMISSION